Fagsprogsforskning i Sovjetunionen - Mikkelsen, Hans Kristian (HERMES - Journal of Language and Communication in Business, 1988)
The author intends to describe main trends in Soviet special language research, which is conceived of as an integrated part of general linguistic stylistics. This style conception can be traced back to the 20'es, though its contemporary functional form mainly can be attributed to V.V. Vinogradov (late 50'es and early 60'es). The following stages can be seen in the exploration of the five functional styles (scientific, official-business, publicistic, colloquial, and artistic): 1) uncovering of special lexical, grammatical, and later, textual features from the individual styles, 2) explanation of these characteristics by means of extralinguistic factors, and 3) differentiation of microstyles within the main (macro-) styles.